Inequality, Output-Inflation Trade-Off and Economic Policy Uncertainty Evidence From South Africa - Ndou, Eliphas; Mokoena, Thabo (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
XXXVII, 507 p. 264 illus., 62 illus. in color.